2022
DOI: 10.1159/000522197
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Gestational Weight Gain Adequacy and Neonatal Outcomes in Tanzania

Abstract: Introduction: Gestational weight gain (GWG) is associated with fetal and newborn health; however, data from sub-Saharan Africa are limited. Methods: We used data from a prenatal micronutrient supplementation trial among a cohort of HIV-negative pregnant women in Dar es Salaam, Tanzania to estimate the relationships between GWG and newborn outcomes. GWG adequacy was defined as the ratio of the total observed weight gain over the recommended weight gain based on the Institute of Medicine body mass index (BMI)-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Compared to the adequate GWG group, the severely inadequate GWG population had higher risk of IUGR (OR 1.27; CI 95% 1.06-1.52) and LBW (OR 1.64; CI 95% 1.24-2.16), along with the inadequate GWG (LBW-OR 1.17; CI 95% 0.87-1.57/IURG-OR 1.2; CI 95% 1.0-1.43). Contrarily, the population with excessive GWG (18%), had a higher prevalence of macrosomia (OR 1.52; CI 95% 1.0-2.31), showing the same pattern found in our study (Figure 1) [28].…”
Section: Discussionsupporting
confidence: 88%
“…Compared to the adequate GWG group, the severely inadequate GWG population had higher risk of IUGR (OR 1.27; CI 95% 1.06-1.52) and LBW (OR 1.64; CI 95% 1.24-2.16), along with the inadequate GWG (LBW-OR 1.17; CI 95% 0.87-1.57/IURG-OR 1.2; CI 95% 1.0-1.43). Contrarily, the population with excessive GWG (18%), had a higher prevalence of macrosomia (OR 1.52; CI 95% 1.0-2.31), showing the same pattern found in our study (Figure 1) [28].…”
Section: Discussionsupporting
confidence: 88%
“…However, these findings relate to gestational weight gain only in the 3 rd trimester of gestation, whereas in the current study, gestational weight gain was obtained from 1 st to 3 rd trimester of gestation. It seems possible that inadequate gestational weight gain may be reflective of nutritional deficiencies particularly during early gestation, which could affect plasma volume expansion and maternal tissue development to support the foetus to term, resulting to preterm delivery [ 39 , 40 ]. Indeed, preterm delivery poses major health complications to babies and increases the risk of neonatal and infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the risk of post-term birth increase with increasing maternal BMI [ 26 ]. We overthrew the systematic review and meta-analyses focused on GWG and infant outcomes, while few pieces of evidence mentioned post-term birth [ 7 , 27 , 28 ]. In the present study, we found that inadequate GWG was associated with a higher risk of post-term birth among mothers with normal weight.…”
Section: Discussionmentioning
confidence: 99%